Analisis Pesan Persuasif Yang Dibangun Oleh Kementerian Kesehatan Melalui Video Cegah, Lawan, Obati Diabetes Di Youtube - Yunita Permatasari; Sophia Bernadette (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2020)
Abstract Health messages are important in the field of public health to encourage behavior change. In 2017, through a “Prevent, Treat, Fight Diabetes” Campaign initiated by the Ministry of Health of the Republic of Indonesia, the Government uploaded a digital video public service advertisement through a you tube account with the username of the Ministry of Health's P2PTM Directorate. This research was conducted to understand how the Persuasion Technique used by the Ministry of Health in building messages contained in the communication campaign carried out through the video. The main question in this connection is how the persuasion technique used in the health campaign "Prevent, Treat, Fight Diabetes" conducted by the Ministry of Health in persuading message recipients? To find out how the Persuasion Technique of a health campaign persuasion message carried out by the Ministry of Health in the “Prevent, Treat, Fight Diabetes” campaign by the Ministry of Health in persuading message recipients, this study uses the theory of Campaign Communication, Social Campaigns, and Persuasion Techniques with a fear approach. to analyze the elements in a persuasive message from the Ministry of Health.